Discipline-Based Art Education in Labanotation Course as a Strategy to Create Graduate Profiles - Imma Fretisari; Agus Cahyono; Hartono Hartono; Trianti Nugraheni (International Conference on Science, Education, and Technology, 2022)
Abstract. The writing of this article aims to describe the results of the analysis of the application of Discipline-Based Art Education (DBAE) in the learning outcomes of the Labanotation course as part of the strategy to create a profile of graduates who have competence in dance and or dance education. The learning achievement of Labanotation is not only as a dance handicapping system, but also can hone analytical skills in dance movements. The research method used is qualitative with a descriptive analysis approach. Based on the results of data processing and analysis that has been carried out, it is concluded that through the DBAE approach the implementation of the Labanotation Course is held with the aim of equipping/preparing students, so that students have skills and insight in writing and reading Labanotation, analyzing dance movements in order to understand the form and shape of dance techniques in dissecting and compiling them. This analytical ability is also needed by students in processing teaching materials and compiling learning methodologies. So it is hoped that by studying Labanotation, students when they graduate will be ready to have qualified competencies in the fields of research, education, and entrepreneurship in accordance with the predetermined graduate profile.